The role of School and Person Old in the Avoid Association Free to Children Age Teens in High school Country 3 The City Cape Hall - Lahmuddin, Lahmuddin; Maisaroh, Rizka (Lembaga Riset Mutiara Akbar, 2022)
A lime is a form of a person's interaction against environment around. A child's child is necessary in control so well not to hapen or in the hangout or fall in to the Association free, so that Pose things that violate the rules that apply social disagrees. Free association among the adolescents today is often therefore It should be noticed by parents especially in order for children to not take action-acts that violate the rules both good government rules and rules in Islam. As with a relationship with the opposite sex that is not his mahram “, Also like using drug drugs. The purpose of this research teknologi wing the role of school in the Association free to Teenagers in SMA Negeri 3 Tanjung Balai City, to know the role of the elderly in avoiding free inter course teenage children. This research Using qualitative methods. Data collection techniques performed by researchers is Interview and observation. As for techniques analysis of the data in the This research uses descriptive techniques, which is in analyzing related with free issues of adolescents among teenagers. Thus, the role school in preventing free associations to teenagers done with three Stages, first preventive, repressive and curative, where students first given directions and information to prevent students to do the problem, more if the prevention not successfully then the teens, will be given the punishment is the coaching through educational punishment, not shaped violence to students. With thus school have the role of an important in the prevent Association free to teenagers. And the role of parents in preventing free intercourse can be by means to give you the attention and needs of the child, which is can be help and prevent free intercourse